Participatory Communication Based on Digital Platforms for Communities in Indonesia - Hamzah Turmudi (GoAcademica Research & Publishing, 2020)
The emergence of participatory communication models is an alternative to conventional development communication practices and theories that are one-way. With a democratic participatory model, civil society can be further involved in social change and support programs that are carried out by stakeholders. This article explains in a simple manner the application of participatory-based development communication in Indonesia and its implementation to digital media through examples of the presence of the Qlue application. Armed with a literature study, this article tries to re-raise the discourse of the importance of the contribution of the study of communication science and the adoption of digital technology for development.